Use the four-step process to find \( s^{\prime}(x) \) and then find \( s^{\prime}(1), s^{\prime}(2) \), and \( s^{\prime}(3) \) \( s(x)=9 x-5 \) \( s^{\prime}(x)=\square \) (Simplify your answer. Use inlegers or fractions for any numbers in the expression.) \( s^{\prime}(1)=\square \) (Type an integer or a simplified fraction.) \( s^{\prime}(2)=\square \) (Type an integer or a simplified fraction.) \( s^{\prime}(3)=\square \) (Type an integer or a simplified fraction.)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To find \( s'(x) \) using the four-step process, we follow these steps: 1. **Identify the function**: Here, \( s(x) = 9x - 5 \). 2. **Apply the power rule**: The derivative of \( ax^n \) is \( nax^{n-1} \). The term \( 9x \) has a derivative of \( 9 \) since the power of \( x \) is 1 and the derivative of a constant is 0. Therefore, \( s'(x) = 9 \). 3. **Verify with increment methods**: Examine \( s(x + h) \) and \( s(x) \): \[ s(x + h) = 9(x + h) - 5 = 9x + 9h - 5 \] \[ s(x + h) - s(x) = (9x + 9h - 5) - (9x - 5) = 9h \] Thus, the average rate of change is \( \frac{9h}{h} = 9 \) as \( h \) approaches 0. 4. **Finalizing the derivative**: This reinforces that \( s'(x) = 9 \). Now we calculate \( s'(1) \), \( s'(2) \), and \( s'(3) \): - \( s'(1) = 9 \) - \( s'(2) = 9 \) - \( s'(3) = 9 \) In summary: \( s'(x) = 9 \) \( s'(1) = 9 \) \( s'(2) = 9 \) \( s'(3) = 9 \)